2020
DOI: 10.14710/jitaa.45.2.103-114
|View full text |Cite
|
Sign up to set email alerts
|

Breast meat characteristics of broilers fed fermented mixture of cassava pulp and Moringa oleifera leaf meal

Abstract: The present study aimed to investigate the effect of feeding fermented mixture of cassava pulp and M. oleifera leaf meal (FCPMO) on the breast meat characteristics of broiler chickens. From day 8 onward, 400 Lohmann broiler chicks were allotted to four dietary groups included CONT (maize-soybean-based feed with no additive), BACI (maize-soybean-based feed supplemented with 0.1% zinc bacitracin), FERM (feed containing 20% of FCPMO) and FERB (feed containing 20% of FCPMO and 0.1% probiotic Bacillus subtilis). At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…No significant differences were found between both nano-thyme and nano-ginger and the control group. This result is in accordance with Sugiharto [ 56 ] who reported that phytogenic supplements may enhance pigment deposition (especially yellow pigment) in broiler chicken meats.…”
Section: Discussionsupporting
confidence: 92%
“…No significant differences were found between both nano-thyme and nano-ginger and the control group. This result is in accordance with Sugiharto [ 56 ] who reported that phytogenic supplements may enhance pigment deposition (especially yellow pigment) in broiler chicken meats.…”
Section: Discussionsupporting
confidence: 92%
“…Also, it was reported that, herbal plants can increases hemoglobin in broiler tissue and support of this, it was suggested levels of 200, 400, 600 and 800 mg/kg turmeric extract improved broilers digestion and metabolism and due to this hemoglobin production was increased in broiler tissue and ultimately produced redder meat in broilers (Sugiharto, 2011). According to these researchers supplementation of chicken's diet whit herbal may enhance pigment deposition in broiler meats especially yellow pigment and it causes the change colour of meat (Sugiharto, 2020).…”
Section: Meat Physical Analysesmentioning
confidence: 86%
“…Poultry meat and egg have valuable nutrients including proteins for human nutrition and a source of income for the community in many development and undevelopment countries therefore; poultry production has a very important role in the economic development of society (Abd El-Hakim et al, 2009). So, poultry production industry focused to optimize growth performance of broiler chicken through better growth rate and improved feed intake and body weight especially after COVID-19 crisis (Al-Khalaifah et al, 2022;Sugiharto et al, 2020). In poultry industry, antibiotics used for many years to stimulate growth and development of broiler and this amount is approximately five times the amount of antibiotics used for disease treatment (Nir and Şenköylü, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…MLM contains essential amino acids and functional proteins that may maintain protein synthesis and muscle development in broiler chickens exposed to HS (Natsir et al, 2019;Islam et al, 2021;Javed et al, 2024). Under normal rearing conditions, feeding broilers with fermented cassava pulp and MLM increased both protein and polyunsaturated fatty acid content (Sugiharto et al, 2020). The broiler's breast muscle contains vital amino acids and unsaturated fatty acids were reported to be dose-increased with MLM supplementation ( Jiang et al, 2023).…”
Section: Advances Inmentioning
confidence: 99%